Walking at the edge: How tempo-spatial nexus forms HRM practices in project-based organizations - Samimi, Ehsan (Frontiers in Psychology, 2023)
Research has scrutinized the role of different HRM practices in PBOs mostly in terms of project success and articulated the challenges of traditional HRM to reconcile with the project context. HRM practices have been addressed less in PBOs with a practice-based research lens, however. Particularly, the role of tempo-spatial nexus in shaping such practices in this organizational form has been under-researched, although PBOs provide a very suitable context for doing so. Drawing upon a comparative case study in the oil and gas industry of Scotland and adopting a practice-based approach, this research aims to shed light on how HRM practices are shaped and re-shaped in the project-based context. The study, specifically, scrutinizes the role of temporality and space in the formation, adoption and adaptation of HRM practices in these organizational forms. The findings reveal that project characteristics, specifically their duration, size and technical properties, induce different temporalities, which are reflected in the pace of practices and, along with different work locations and inter-organizational relationships, impact HRM practices as a threefold structure.